2013
DOI: 10.1101/gad.205278.112
|View full text |Cite
|
Sign up to set email alerts
|

Mouse TU tagging: a chemical/genetic intersectional method for purifying cell type-specific nascent RNA

Abstract: Transcriptional profiling is a powerful approach for understanding development and disease. Current cell type-specific RNA purification methods have limitations, including cell dissociation trauma or inability to identify all RNA species. Here, we describe ''mouse thiouracil (TU) tagging,'' a genetic and chemical intersectional method for covalent labeling and purification of cell type-specific RNA in vivo. Cre-induced expression of uracil phosphoribosyltransferase (UPRT) provides spatial specificity; injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
171
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(173 citation statements)
references
References 37 publications
(51 reference statements)
2
171
0
Order By: Relevance
“…Recently, a complementary approach to isolating RNA from cells labeled by Cre was reported, in which Cre-activated transgenic expression of uracil phosphoribosyltransferase (UPRT) permits selective RNA labeling by thiouracil (TU tagging) (7). A strength of the TU-tagging strategy is the enhanced temporal resolution for active transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a complementary approach to isolating RNA from cells labeled by Cre was reported, in which Cre-activated transgenic expression of uracil phosphoribosyltransferase (UPRT) permits selective RNA labeling by thiouracil (TU tagging) (7). A strength of the TU-tagging strategy is the enhanced temporal resolution for active transcription.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, approaches have been developed to isolate RNAs from selected cell types and/or selected transcript fractions (4)(5)(6)(7). Often these approaches involve tissue dissociation followed by FACS, but this is slow and the dissociation procedure itself likely alters expression profiles.…”
mentioning
confidence: 99%
“…We found that DACH1 could fulfill this purpose. This homolog to the Drosophila protein Dachshund was initially identified in a screen that used Creinducible TU-tagging of RNA to discover endothelial-specific genes from whole hearts (Gay et al, 2013). Commercially available antibodies to DACH1 are specific, as evidenced by the absence of immunostaining in hearts from knockout animals (supplementary material Fig.…”
Section: Apjcreer Can Be Used To Lineage Trace Sv-derived Coronary Vementioning
confidence: 99%
“…Genetically encoded phosphoribosyltransferase (UPRT) biosynthetically labels nascent RNA in the target cell type when provided with 4-thiouracil. Chemically modified RNA molecules can then be affinity purified, a technique called TU-tagging (Miller et al, 2009;Gay et al, 2013). Alternatively, mRNA-binding proteins can be affinity tagged in specific cells and used as anchors to co-purify associated mRNAs.…”
Section: Introductionmentioning
confidence: 99%